Metode Pembentukan Karakter Tanggung Jawab Santri di Taman Pendidikan Al-Qur’an Surau Balenggek Sikabu Bukit Lubuk Alung - Ferzania Ferzania; Murniyetti Murniyetti (FONDATIA, 2022)
One method that can assist students in achieving learning goals is that a method is needed to make it easier for someone to carry out, this study aims to find out how the teacher's method, inhibiting and supporting factors and the teacher's efforts in shaping the character of the responsibility of students at TPA Surau Balenggek Sikabu Bukit Lubuk Alung, Padang Pariaman Regency. This study uses qualitative research methods with the type of field research. Sources of data were taken from several informants through in-depth interviews selected using purposive sampling technique. To obtain the results of interviews, this study used interview guidelines as a research instrument. Data collection techniques used are observation, interviews and documentation. While the data analysis technique that the author uses is the process of data reduction, data presentation (Data Display) and verification/drawing conclusions. Overall the results of this study show; The first method is the teacher's method in shaping the character of the responsibility of students at TPA Surau Balenggek Sikabu Bukit Lubuk Alung, Padang Pariaman Regency, including: a) the exemplary method, the teacher acts as a role model for students in the form of words, actions, words and things that are material and spiritual. b) The habituation method, the teacher familiarizes the students to always give assignments to the students in the form of rote memorization then deposited with the teacher and recorded, and assessed. c) Advice Method, the teacher gives advice by repeating what has been advised. Second, inhibiting and supporting factors consisting of Information and Technology Media in the form of HP, Internal factors (internal) the emergence of a sense of laziness in students, lack of attention from parents, lack of support and motivation from students' parents and environmental factors where students live such as play environment in the daily life of students, while the supporting factors are teachers and parents. Third, the teacher's efforts in shaping the character of the responsibility of students are to provide motivation and advice, the teacher gives encouragement and advises about the duties and importance of the character of responsibility, and the teacher must be patient. Collaborating with parents, teachers collaborate directly with students' parents regarding assignments and the learning process. Checking assignments and giving sanctions, teachers checking students' assignments and giving punishments for students who don't make assignments and don't follow religious programs.